Assessment of Status and Sustainability Index for Smallholder Rubber Plantation in Riau Province of Indonesia - Budi Azwar; Rozi Andrini; Ahmad Hamdalah; Fitra Lestari Norhiza; Rika Taslim; Juandi Muhammad (School of Postgraduate Studies, Diponegoro Univer, 2025)
The conversion of rubber plantation to oil palm cultivation in Riau province is raising concerns regarding the decline of rubber commodity. Historically, the province has been a key producer of such commodity in Indonesia. The community-owned rubber plantation, on the other hand, is diminishing, leading to a troubling cycle that makes it difficult to establish environmentally sustainable programs. Therefore, this research aimed to assess sustainability of smallholder rubber plantation in Riau. It was observed that the comprehensive RapRubber analysis yielded an index of 39.76, classifying status as less sustainable. The results showed that the management of rubber plantation was under pressure. In a more detailed analysis, the ecological dimension had an index of 43.22, placing it in the less sustainable category. The economic dimension scored 50.80, signifying a relatively sustainable status. In contrast, the social dimension reduced with an index of 25.25, classifying it as less sustainable. The attributes that contributed to the unsustainability of the ecological dimension were fire frequency and by-products, while the factors contributing to less sustainability of the social dimension included the initial land-clearing methods, preservation practices, and local wisdom. In the economic dimension, land status and pricing were essential determinants of sustainability.